Nasal canine defect resolution by means of a flap obtained from the patient's ear (Veterinary Science, 2017)
The authors report the surgical resolution of a nasal defect in a dolichocephalic female dog, by means of a flap obtained from the patient's ear. The nasal defect involved skin and nasal bone, had been produced 30 days before consultation and was related to an oronasal fistula at the level of the fourth premolar. The defect had an oval form of 3x5 cm, through which the inner part of the nasal cavity and the ethmoid bone could be seen. The defect produced profuse nasal secretion and respiratory disorder in the animal. After treating the oronasal fistula, an auricular flap was created in different, successive interventions. The procedure consisted in suturing the edge of the ear to the edge of the defect with a simple suture so that the ear could be dissected later. The flap cured the defect. The dog wore an Elizabethan collar during the weeks of treatment since the ear remained bent towards the defect until it was fully dissected. The subsequent dissection of the ear in different stages permitted the substitution of the blood supply with the blood coming from the capillaries of the edge of the defect. The restorative surgery offered a plastic and functional solution to the nose.
Keywords: Dog; Plastic surgeri; Flap; Ear